Real-Time Weigh In Motion (WIM) Monitoring System Based on Optoelectronics and Whatsapp Gateway - Fatimah Nur Hidayah; Agus Jamaldi; Samuel Ardhi Krisitiawan (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
The increasing mobility of motorized vehicles, such as trucks, has positively contributed to regional growth and connectivity in Indonesia. However, this development has also introduced significant challenges, particularly road damage caused by overloaded vehicles. Such damage not only jeopardizes the safety of road users but also incurs substantial economic costs due to infrastructure maintenance and repair. This research utilizes a real-time Weigh-In-Motion (WIM) monitoring system based on optoelectronic technology and a WhatsApp gateway. By combining the precision of optoelectronic sensors with the accessibility of communication through WhatsApp, this system aims to accurately and promptly detect overloaded vehicles. The study focuses on integrating the real-time WIM monitoring system with optoelectronic devices and WhatsApp-based communication. The methodology involves applying varying loads to the fiber optic sensor system, ranging from 1 kg to 10 kg, with loading time variations of 100 ms, 250 ms, 500 ms, 750 ms, and 1000 ms. The programming aspect uses Arduino and Virtual Basic (VB) to support the hardware system for real-time detection by the optoelectronic components. The results demonstrate that the developed fiber optic sensor performs optimally, as evidenced by the data trendline showing alignment at the same point during both ascending and descending conditions. Furthermore, the system successfully provides user notifications via WhatsApp when detecting threshold data at a load of 6 kg crossing the fiber optic sensor system.